The Role of Arginase and some Parameters in Diabetic Type 2 Patients with and without Retinopathy - Yassen, Maha F.; Khaleel, Fayhaa. M. (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Oxidative stress plays a major role in the pathogenesis of diabetes mellitus by damaging cellular organelles and enzymes in blood such as arginase1, insulin and glutathione s-transferase; increasing lipid peroxidation such as malondialdehyde and increasing insulin resistance which can lead to diabetic complications such as diabetic retinopathy. Objectives: To explore the relationship of oxidative stress to the development of diabetic retinopathy by measuring the levels of Arginase1, the activity of glutathione s-transferase enzyme, and the levels of malondialdehyde as a secondary product of lipid peroxidation (biomarker for oxidative stress). Patients and MethodsThis study was conducted from November 2022 to January 2023 at the Ibn Al-Haitham Teaching Eye Hospital in Baghdad, the University of Baghdad / Department of Chemistry and the National Diabetes Centre for Treatment and Research at Al-Mustansyrriah University. This study was conducted on 120 subjects distributed as follows: 40 non-diabetic obese controls, 40 type 2 diabetics with no retinopathy, and 40 type 2 diabetic retinopathy patients, between 30 and 65 years of age. All groups were subjected to tests: measuring fasting blood glucose (FBG), HbA1c, lipid profile (cholesterol, triglycerides, HDL- cholesterol, LDL- cholesterol, and VLDL cholesterol), serum total arginase1, malondialdehyde glutathione s -transferase, body mass index (BMI), and waist-to-hip ratio. Results: Mean arginase1 levels were significantly higher in diabetic patients than in diabetic retinopathy and control groups (p ≤ 0.05). The mean xidative stress marker malondialdehyde concentration was significantly higher in diabetic retinopathy patients than in type 2 diabetics and the control group (P ≤ 0.05). The mean glutathione s-transferase activity in diabetic retinopathy patients was significantly higher than in the control group and type 2 diabetics (P ≤ 0.05). Conclusion: There is a relationship between oxidative stress and the development of diabetic retinopathy, where the levels of arginase1 and malondialdehyde increased and the activity of glutathione s –transferase enzyme increased as a result of oxidative stress and inflammation associated with complications of type 2 diabetes.